A heat-resistant, impact-resistant, flex-resistant cable sheath material and a preparation method thereof

By using silane crosslinked polyethylene and olefin copolymers in cable sheath materials, combining inorganic fillers and glass fibers, and adding relevant additives, the existing cable sheath materials are solved in terms of impact resistance, heat resistance and The lack of flexibility has achieved efficient thermal stability and mechanical properties.

CN118895022BActive Publication Date: 2025-02-07西部电缆陕西有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411401623.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-07
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Existing cable sheath materials are difficult to take into account both impact resistance, heat resistance and flexibility in high-voltage cables, especially in cases of frequent bending and stretching.

Method used

Using silane crosslinked polyethylene and olefin copolymer as base material, combined with inorganic fillers and alkali-free glass fibers, and added heat stabilizers, plasticizers, antioxidants and light stabilizers, and through specific hot and cold pressing treatment , prepare heat and impact-resistant flexural cable sheath material.

Benefits of technology

It significantly improves the heat resistance, impact resistance and mechanical properties of the cable sheath material, while maintaining high flexibility resistance, and is suitable for high voltage cable applications in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118895022B_ABST
    Figure CN118895022B_ABST
Patent Text Reader

Abstract

The invention discloses a heat-resistant, impact-resistant and flex-resistant cable sheath material and a preparation method thereof, belonging to the technical field of cable sheath materials, and used to solve the technical problem that in the prior art, excessive inorganic reinforcing additives are added to improve the heat resistance and impact resistance of the cable sheath material, but the flex resistance of the cable sheath material is significantly reduced. The invention comprises silane cross-linked polyethylene, olefin copolymer, mixed inorganic filler, alkali-free glass fiber, heat stabilizer, plasticizer, antioxidant and light stabilizer, polysilicon chlorine organic body and polyethylene are cross-linked by polycondensation to obtain silane cross-linked polyethylene, which contains polybenzene, chlorine and silicon elements, thereby improving its own heat resistance and impact resistance, butadiene epoxy resin and methacrylic acid undergo addition reaction to obtain olefin copolymer, which can relax the rigidity of the silane cross-linked polyethylene and improve its own flex resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable materials, and in particular to a heat-resistant, impact-resistant, flex-resistant cable sheath material and a preparation method thereof. Background Art

[0002] In the research on high-voltage cable structure, the main insulation layer as the core structure has always been the focus of research, while the research on the outer sheath is relatively less. Since the outer sheath of the high-voltage cable is in direct contact with the external environment, the requirements for the heat resistance, impact resistance and flexural resistance of the cable sheath material are higher in a relatively harsh environment.

[0003] Polyethylene is a commonly used cable material. Polyethylene cables have the characteristics of high mechanical strength and excellent chemical corrosion resistance. In order to further improve the impact resistance and heat resistance of polyethylene cables, a certain amount of inorganic fillers or glass fibers and other reinforcing agents are added to the outer sheath material; however, the above-mentioned reinforcing agents will reduce the flexibility of the outer sheath material, making it difficult for the cable sheath material to withstand frequent bending and stretching in actual use. How to design the cable sheath material components so that the polyethylene cable material has high impact resistance and heat resistance while still having a certain flexibility resistance is still a technical problem that needs to be solved urgently.

[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0005] The object of the present invention is to provide a heat-resistant, impact-resistant and flexural-resistant cable sheath material and a preparation method thereof, so as to solve the technical problem of poor flexural resistance of cable sheath materials doped with reinforced materials and heat-resistant materials in the prior art.

[0006] The purpose of the present invention can be achieved by the following technical scheme: a heat-resistant, impact-resistant and flex-resistant cable sheath material, which comprises, by weight, 50-60 parts of silane cross-linked polyethylene, 20-30 parts of olefin copolymer, 5-10 parts of mixed inorganic filler, 1-2 parts of alkali-free glass fiber, 1-2 parts of heat stabilizer, 1-2 parts of plasticizer, 1-2 parts of antioxidant and 1-2 parts of light stabilizer.

[0007] The cable sheath material is prepared by taking silane cross-linked polyethylene and olefin copolymer as the base materials of the sheath material, mixing inorganic fillers and alkali-free glass fibers as reinforcing agents, and adding relevant additives.

[0008] Furthermore, the preparation method of the silane cross-linked polyethylene comprises the following steps:

[0009] A1. 4-tert-butylcatechol and carbon tetrachloride are mixed and dissolved to obtain a 4-tert-butylcatechol solution; one side of a three-necked round-bottom flask is connected to an experimental packing column, the upper end of the packing column is connected to a condenser, and the lower end is connected to a reflux bottle; the condenser is passed through cooling medium water, and the reflux bottle is filled with 1 / 3 volume of petroleum ether; the reflux bottle is connected to a heating device, and the temperature is set to 30-40°C;

[0010] A2. The two ports of the three-necked flask are connected to a dropper measuring bottle, which is respectively filled with p-tert-butylcatechol solution and trichlorosilane, and slowly added to the three-necked round-bottom flask at a rate of 1 mL / min; after the addition is completed, the three-necked flask is refluxed at 25-30° C. for 4-6 hours, and the by-product hydrogen chloride gas is discharged through the condenser of the packed column; then the three-necked flask is heated to 80-85° C. until all the organic liquid is evaporated, and the solid product at the bottom of the three-necked flask is collected; the solid product is washed with deionized water and vacuum dried at 70-80° C. to constant weight to obtain a polysilicon chlorine organic body;

[0011] The polysilicic acid chloroorganic compound is prepared by nucleophilic substitution of tert-butylcatechol and trichlorosilane.

[0012] The reaction equation of tert-butylcatechol and trichlorosilane is as follows:

[0013]

[0014] A3, polysilicon chloride organic body, initiator, polyethylene and water are mixed, polycondensed and cross-linked at 70-80°C for 24 hours, and then filtered to obtain silane cross-linked polyethylene.

[0015] Dibutyltin dilaurate is used as a peroxide initiator. The peroxide initiator decomposes when heated to become free radicals with high chemical activity. These free radicals can capture hydrogen atoms on the polyethylene main chain to generate active free radicals, which then undergo grafting reaction with polysilicon chlorine organic bodies. The grafted polyethylene undergoes hydrolysis and condensation to form -Si- under the catalysis of dibutyltin dilaurate, and silane cross-linked polyethylene is prepared through condensation cross-linking.

[0016] Furthermore, in step A1, the ratio of p-tert-butylcatechol to carbon tetrachloride is 20-30 g:50 mL; in step A2, the amount of p-tert-butylcatechol solution is 70-80 mL, and the amount of trichlorosilane is 5-10 g.

[0017] Furthermore, in step A3, the initiator is dibutyltin dilaurate; the usage ratio of polysilicon chloride organic body, initiator, polyethylene and water is 50-60g:1-3g:300g:500mL.

[0018] Furthermore, the preparation method of the olefin copolymer comprises the following steps:

[0019] The epoxidized polybutadiene resin, methacrylic acid and an initiator are mixed and reacted at 30-40° C. for 3-5 hours to obtain a product; the product is filtered using a filter cloth to remove the initiator solids to obtain an olefin copolymer.

[0020] Under the action of an initiator, an epoxidized polybutadiene resin and methacrylic acid undergo addition polymerization to prepare an olefin copolymer.

[0021] Furthermore, the initiator is an aqueous solution of ammonium persulfate, which is obtained by uniformly mixing 1-3 g of ammonium persulfate and 30 mL of deionized water; the usage ratio of the epoxidized polybutadiene resin, methacrylic acid and catalyst is 50-100 g:10-20 g:1-3 g.

[0022] Furthermore, the mixed inorganic filler is prepared by the following steps:

[0023] Diatomaceous earth, fly ash floating beads, 0.2-1 mm alumina hollow microspheres, and 0.5-1 mm magnesium oxide hollow microspheres are uniformly mixed to obtain a mixture; the mixture is ground to 100-200 nm to obtain a mixed inorganic filler.

[0024] The invention uses powdered heat-insulating refractory material diatomite, fly ash floating beads and oxide hollow microspheres as components, mixes them evenly, and prepares a mixed inorganic filler.

[0025] Furthermore, the diameter of the alkali-free glass fiber is 10-20 μm; the heat stabilizer is obtained by mixing dibutyltin maleate and phosphite in a mass ratio of 3-2:1; the plasticizer is a phthalate plasticizer, specifically any one of methyl phthalate, ethyl phthalate or butyl phthalate; the antioxidant is obtained by mixing antioxidant 1010 and antioxidant DSTP in a mass ratio of 2-3:1; the light stabilizer is obtained by mixing UV-9 and UV-531 in a mass ratio of 1:1.

[0026] As another aspect of the present invention, the present invention also provides a method for preparing a heat-resistant, impact-resistant, and flex-resistant cable sheath material, comprising the following steps:

[0027] B1, uniformly mixing silane cross-linked polyethylene, olefin copolymer, mixed inorganic filler, alkali-free glass fiber, heat stabilizer, plasticizer, antioxidant and light stabilizer to obtain a mixture;

[0028] B2. The mixed materials are melt-blended on a double-roll mill to obtain a sample; the sample is placed on a flat vulcanizer for hot pressing and cold pressing in sequence, and then naturally cooled to room temperature to obtain a heat-resistant, impact-resistant, and flex-resistant cable sheath material.

[0029] Furthermore, in step B2, the temperature of melt blending is 100-110°C, and the time of melt blending is 10 min; the temperature of hot pressing is 110-120°C, the pressure of hot pressing is 10-20 MPa, and the time of hot pressing is 3-5 min; the temperature of cold pressing is 25°C, the pressure of cold pressing is 10 MPa, and the time of cold pressing is 3-5 min.

[0030] The present invention has the following beneficial effects:

[0031] The present invention uses silane cross-linked polyethylene and olefin copolymer as the base materials of cable sheath materials, uses mixed inorganic fillers and alkali-free glass fibers as reinforcing additives, and adds relevant additives to prepare heat-resistant, impact-resistant and flex-resistant cable sheath materials. Tert-butyl catechol and trichlorosilane undergo nucleophilic substitution reaction to obtain polysilicon-chlorine organic bodies containing multiple benzene rings and multiple silicon elements; polyethylene and polysilicon-chlorine organic bodies are cross-linked by polycondensation to prepare silane cross-linked polyethylene. Since silane cross-linked polyethylene contains high content of benzene rings, silicon and chlorine elements, the flame retardancy and mechanical properties of silane cross-linked polyethylene are improved as a whole, which is manifested as a significant improvement in the heat resistance, wear resistance and impact resistance of silane cross-linked polyethylene. However, the hardness of silane cross-linked polyethylene is too high and brittle fracture is easily generated. Therefore, the present invention uses the addition product of epoxidized polybutadiene resin and methacrylic acid-olefin copolymer as another base material component. In addition, the epoxy groups in the olefin copolymer can react with the unreacted chlorine elements in the polysilicon chlorine organic body, thereby enhancing the cross-linking between the two components of the base material, thereby improving the thermal stability and rigidity of the prepared cable sheath material.

[0032] The cable sheath material prepared by the present invention also includes reinforcing additives, mixed inorganic fillers and alkali-free glass fibers; the mixed inorganic fillers include diatomite, fly ash beads and metal oxide hollow microspheres. Diatomite, as a raw material for medium and high temperature insulation materials, shrinks only 0.1%-0.3% at 50-250°C, and at 50-250°C, the water will be completely evaporated, forming countless pores inside; in addition, the pores of diatomite are very fine, and have a good shielding effect on heat. Fly ash beads are glass hollow microspheres formed after melting and cooling and solidification in high-temperature flames, and have excellent heat-resistant and heat-insulating properties; and the safe use temperature of oxide hollow microspheres is high, and they can withstand the impact of high-temperature flames. Adding the above-mentioned mixed inorganic fillers to the raw materials of the cable sheath material can improve the heat resistance of the cable sheath material. Alkali-free glass fiber has high tensile strength, low elongation at break, and good chemical stability. A certain amount of alkali-free glass fiber can be used as a reinforcing material for the cable sheath material. The reinforcing additive can significantly improve the heat resistance and impact strength of the cable sheath material.

[0033] In order to avoid degradation caused by unstable structures such as side chains and double bonds contained in silane cross-linked polyethylene and olefin copolymers under the action of heat and high temperature, a certain amount of heat stabilizer is added to the prepared cable sheath material. The present invention uses organic tin dibutyltin maleate as a heat stabilizer. Organic tin has the function of capturing free radicals; in addition, organic tin can also terminate with other free radicals, thereby reducing the unstable factors in the molecular chain of the main material. As an auxiliary heat stabilizer, phosphite has the function of capturing hydrogen chloride and decomposing peroxides, thereby improving the thermal stability of chlorosilane cross-linked polyethylene. The addition of mixed antioxidants and mixed light stabilizers can improve the stability of the prepared cable sheath material under special and complex environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 The present invention provides a flow chart for preparing the heat-resistant, impact-resistant and flex-resistant cable sheath material. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Embodiment 1: This embodiment provides a method for preparing a silane cross-linked polyethylene for a heat-resistant, impact-resistant, flex-resistant cable sheath material, comprising the following steps:

[0038] A1, 20g of p-tert-butylcatechol and 50mL of carbon tetrachloride were mixed and dissolved to obtain a p-tert-butylcatechol solution; one side of a 250mL three-necked round-bottom flask was connected to an experimental packing column, the upper end of the packing column was connected to a condenser, and the lower end was connected to a reflux bottle; the condenser was passed through a cooling medium of water, and the reflux bottle was filled with 1 / 3 volume of petroleum ether; the reflux bottle was connected to a heating device electric furnace, and the temperature of the electric furnace was set to 40°C to keep the petroleum ether in a reflux state.

[0039] A2. Both side ports of the three-necked round-bottom flask are connected to 100mL dropping measuring bottles. The two dropping measuring bottles are respectively filled with 70mL of p-tert-butylcatechol solution and 5g of trichlorosilane. An electric heating furnace is set at the bottom of the three-necked round-bottom flask, and the temperature of the electric heating furnace is adjusted to 25°C. P-tert-butylcatechol solution and trichlorosilane are slowly added to the three-necked round-bottom flask at 1mL / min, and reflux reaction is carried out in the three-necked round-bottom flask for 4h. During this period, the by-product HCl gas is discharged through the condenser at the upper end of the packed column. The three-necked round-bottom flask is heated to 80°C until all the organic liquid is evaporated, and the solid product at the bottom of the three-necked round-bottom flask is collected. The solid product is washed with deionized water and vacuum dried at 70°C to constant weight to obtain a polysilicon chlorine organic body;

[0040] A3. Add 50g polysilicon chlorine organic body, 3g initiator dibutyltin dilaurate, 300g polyethylene and 500mL water into a 1000mL beaker, and stir at 1000r / min for 5min. Then transfer the beaker to a water bath, adjust the temperature of the water bath to 70℃, perform polycondensation crosslinking at this temperature for 24h, and then filter to obtain silane crosslinked polyethylene.

[0041] Embodiment 2: This embodiment provides a method for preparing a silane cross-linked polyethylene for a heat-resistant, impact-resistant, flex-resistant cable sheath material, comprising the following steps:

[0042] A1, 25g of p-tert-butylcatechol and 50mL of carbon tetrachloride were mixed and dissolved to obtain a p-tert-butylcatechol solution; one side of a 250mL three-necked round-bottom flask was connected to an experimental packing column, the upper end of the packing column was connected to a condenser, and the lower end was connected to a reflux bottle; the condenser was passed through a cooling medium of water, and the reflux bottle was filled with 1 / 3 volume of petroleum ether; the reflux bottle was connected to a heating device electric furnace, and the temperature of the electric furnace was set to 43°C to keep the petroleum ether in a reflux state.

[0043] A2. Both side ports of the three-necked round-bottom flask are connected to 100mL dropping measuring bottles. The two dropping measuring bottles are respectively filled with 75mL of p-tert-butylcatechol solution and 6g of trichlorosilane. An electric heating furnace is set at the bottom of the three-necked round-bottom flask, and the temperature of the electric heating furnace is adjusted to 28°C. The p-tert-butylcatechol solution and trichlorosilane are slowly added to the three-necked round-bottom flask at 1mL / min, and the reflux reaction is carried out in the three-necked round-bottom flask for 5h. During this period, the by-product HCl gas is discharged through the condenser at the upper end of the packed column. The three-necked round-bottom flask is heated to 80°C until all the organic liquid is evaporated, and the solid product at the bottom of the three-necked round-bottom flask is collected. The solid product is washed with deionized water and vacuum dried at 73°C to constant weight to obtain a polysilicon chlorine organic body;

[0044] A3. Add 55g polysilicon chlorine organic body, 3g initiator dibutyltin dilaurate, 300g polyethylene and 500mL water into a 1000mL beaker, and stir at 1000r / min for 6min. Then transfer the beaker to a water bath, adjust the temperature of the water bath to 75℃, perform polycondensation crosslinking at this temperature for 24h, and then filter to obtain silane crosslinked polyethylene.

[0045] Embodiment 3: This embodiment provides a method for preparing a silane cross-linked polyethylene for a heat-resistant, impact-resistant, flex-resistant cable sheath material, comprising the following steps:

[0046] A1. 30 g of p-tert-butylcatechol and 50 mL of carbon tetrachloride were mixed and dissolved to obtain a p-tert-butylcatechol solution; one side of a 250 mL three-necked round-bottom flask was connected to an experimental packing column, the upper end of the packing column was connected to a condenser, and the lower end was connected to a reflux bottle; the condenser was passed through a cooling medium of water, and the reflux bottle was filled with 1 / 3 volume of petroleum ether; the reflux bottle was connected to a heating device electric furnace, and the temperature of the electric furnace was set to 50° C. to keep the petroleum ether in a reflux state.

[0047] A2. Both side ports of the three-necked round-bottom flask are connected to 100mL dropping measuring bottles. The two dropping measuring bottles are respectively filled with 80mL of p-tert-butylcatechol solution and 10g of trichlorosilane. An electric heating furnace is set at the bottom of the three-necked round-bottom flask, and the temperature of the electric heating furnace is adjusted to 30°C. P-tert-butylcatechol solution and trichlorosilane are slowly added to the three-necked round-bottom flask at 1mL / min, and reflux reaction is carried out in the three-necked round-bottom flask for 6h. During this period, the by-product HCl gas is discharged through the condenser at the upper end of the packed column. The three-necked round-bottom flask is heated to 80°C until all the organic liquid is evaporated, and the solid product at the bottom of the three-necked round-bottom flask is collected. The solid product is washed with deionized water and vacuum dried at 80°C to constant weight to obtain a polysilicon chlorine organic body;

[0048] A3. Add 60g polysilicon chlorine organic body, 5g initiator dibutyltin dilaurate, 300g polyethylene and 500mL water into a 1000mL beaker, and stir at 1000r / min for 10min. Then transfer the beaker to a water bath, adjust the temperature of the water bath to 80℃, perform polycondensation crosslinking at this temperature for 24h, and then filter to obtain silane crosslinked polyethylene.

[0049] Embodiment 4: This embodiment provides a method for preparing a heat-resistant, shock-resistant, and flex-resistant cable sheath material, comprising the following steps:

[0050] B1, 1g of ammonium persulfate and 30mL of deionized water were mixed evenly to obtain an ammonium persulfate aqueous solution; 50g of epoxidized polybutadiene resin, 10g of methacrylic acid and 30mL of ammonium persulfate aqueous solution were added to a 250mL three-necked reaction bottle, and polyaddition reaction was carried out at 30°C to obtain a product. The product was distilled under reduced pressure at 95°C and -0.1MPa to remove deionized water, and then the ammonium persulfate solid was filtered with a filter cloth while hot to obtain an olefin copolymer.

[0051] B2, diatomaceous earth, fly ash floating beads, 0.2 mm alumina hollow microspheres, and 0.5 mm magnesium oxide hollow microspheres are mixed evenly to obtain a mixture, and the mixture is ground to 100 nm to obtain a mixed inorganic filler.

[0052] B3, dibutyltin maleate and phosphite are uniformly mixed in a mass ratio of 2:1 to obtain a heat stabilizer; antioxidant 1010 and antioxidant DSTP are mixed in a mass ratio of 2:1 to obtain an antioxidant; UV-9 and UV-531 are mixed in a mass ratio of 1:1 to obtain a light stabilizer; according to weight parts, 55 parts of silane cross-linked polyethylene prepared in Example 3, 25 parts of olefin copolymer, 8 parts of mixed inorganic fillers, 2 parts of alkali-free glass fiber with a diameter of 10 μm, 2 parts of heat stabilizer, 2 parts of methyl phthalate, 1 part of antioxidant and 1 part of light stabilizer are mixed to obtain a mixture.

[0053] B4. Add the mixture to an electric heating double-roll open mill, melt blend at 100°C for 10 minutes to obtain a sample. Place the sample on a flat vulcanizer, hot press at 110°C and 10MPa for 3 minutes, then cold press at 10MPa for 3 minutes, take out the sample and naturally cool it to room temperature to obtain a heat-resistant, impact-resistant, and flex-resistant cable sheath material.

[0054] Embodiment 5: This embodiment provides a method for preparing a heat-resistant, shock-resistant, and flex-resistant cable sheath material, comprising the following steps:

[0055] B1, 2g ammonium persulfate and 30mL deionized water were mixed evenly to obtain an ammonium persulfate aqueous solution; 50g epoxidized polybutadiene resin, 15g methacrylic acid and 30mL ammonium persulfate aqueous solution were added to a 250mL three-necked reaction bottle, and polyaddition reaction was carried out at 35°C for 56h to obtain a product. The product was distilled under reduced pressure at 95°C and -0.1MPa to remove deionized water, and then the ammonium persulfate solid was filtered with a filter cloth while hot to obtain an olefin copolymer.

[0056] B2, diatomaceous earth, fly ash floating beads, 0.5 mm alumina hollow microspheres, and 0.6 mm magnesium oxide hollow microspheres are mixed evenly to obtain a mixture, and the mixture is ground to 150 nm to obtain a mixed inorganic filler.

[0057] B3, dibutyltin maleate and phosphite are uniformly mixed in a mass ratio of 2:1 to obtain a heat stabilizer; antioxidant 1010 and antioxidant DSTP are mixed in a mass ratio of 3:1 to obtain an antioxidant; UV-9 and UV-531 are mixed in a mass ratio of 1:1 to obtain a light stabilizer; in parts by weight, 55 parts of silane cross-linked polyethylene prepared in Example 3, 25 parts of olefin copolymers, 8 parts of mixed inorganic fillers, 2 parts of alkali-free glass fibers with a diameter of 15 μm, 2 parts of heat stabilizers, 2 parts of ethyl phthalate, 1 part of antioxidant and 1 part of light stabilizer are mixed to obtain a mixture.

[0058] B4. Add the mixture to an electric heating double-roll open mill, melt blend at 105°C for 10 minutes to obtain a sample. Place the sample on a flat vulcanizer, hot press at 115°C and 15MPa for 4 minutes, then cold press at 10MPa for 4 minutes, take out the sample and naturally cool it to room temperature to obtain a heat-resistant, impact-resistant, and flex-resistant cable sheath material.

[0059] Embodiment 6: This embodiment provides a method for preparing a heat-resistant, shock-resistant, and flex-resistant cable sheath material, comprising the following steps:

[0060] B1, 3g of ammonium persulfate and 30mL of deionized water were mixed evenly to obtain an ammonium persulfate aqueous solution; 100g of epoxidized polybutadiene resin, 20g of methacrylic acid and 30mL of ammonium persulfate aqueous solution were added to a 250mL three-necked reaction bottle, and polyaddition reaction was carried out at 40°C for 6h to obtain a product. The product was distilled under reduced pressure at 100°C and -0.1MPa to remove deionized water, and then the ammonium persulfate solid was filtered with a filter cloth while hot to obtain an olefin copolymer.

[0061] B2, diatomaceous earth, fly ash floating beads, 1 mm alumina hollow microspheres, and 1 mm magnesium oxide hollow microspheres are mixed evenly to obtain a mixture, and the mixture is ground to 200 nm to obtain a mixed inorganic filler.

[0062] B3, dibutyltin maleate and phosphite are uniformly mixed in a mass ratio of 2:1 to obtain a heat stabilizer; antioxidant 1010 and antioxidant DSTP are mixed in a mass ratio of 3:1 to obtain an antioxidant; UV-9 and UV-531 are mixed in a mass ratio of 1:1 to obtain a light stabilizer; according to weight parts, 60 parts of silane cross-linked polyethylene prepared in Example 3, 20 parts of olefin copolymer, 10 parts of mixed inorganic filler, 2 parts of alkali-free glass fiber with a diameter of 20 μm, 2 parts of heat stabilizer, 2 parts of butyl phthalyl glycolate, 2 parts of antioxidant and 2 parts of light stabilizer are mixed to obtain a mixture.

[0063] B4. Add the mixture to an electric heating double-roll open mill, melt blend at 110°C for 10 minutes to obtain a sample. Place the sample on a flat vulcanizer, hot press at 120°C and 20MPa for 5 minutes, then cold press at 10MPa for 5 minutes, take out the sample and naturally cool it to room temperature to obtain a heat-resistant, impact-resistant, and flex-resistant cable sheath material.

[0064] Comparative Example 1: The difference between this comparative example and Example 6 is that the olefin copolymer is replaced by an epoxidized polybutadiene resin of equal mass.

[0065] Comparative Example 2: The difference between this comparative example and Example 6 is that polyethylene of equal mass is used to replace the silane cross-linked polyethylene.

[0066] Comparative Example 3: This comparative example differs from Example 6 in that no mixed inorganic filler is added.

[0067] Performance testing;

[0068] 1. The heat-resistant, impact-resistant and flex-resistant cable sheath materials prepared in Examples 4-6 and Comparative Examples 1-3 were cut into samples with a diameter of 30 mm and a thickness of 2 mm; the samples were placed in a blast drying oven at 160° C. for a thermal oxygen aging test, the test time was 300 h, and the accuracy of the balance used in the test was 0.1 mg; the mass loss rate was calculated as follows:

[0069] in, is the mass loss rate; m0 is the initial mass of the sample, and m is the mass of the sample after thermal oxidation aging.

[0070] 2. According to GB / T1040-2006 "Determination of tensile properties of plastics", the tensile strength and elongation at break of the heat-resistant, shock-resistant and flexural-resistant cable sheath materials prepared in Examples 4-6 and Comparative Examples 1-3 were tested using a CMT4103 microcomputer-controlled electronic universal testing machine.

[0071] 3. The heat-resistant, impact-resistant, and flexural-resistant cable sheath materials prepared in Examples 4-6 and Comparative Examples 1-3 are cut into standard samples with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm; the impact toughness values ​​of the heat-resistant, impact-resistant, and flexural-resistant cable sheath materials prepared in Examples 4-6 are tested using an XJUD-5.5 electronic cantilever beam impact testing machine.

[0072] 4. The notched impact strength of the heat-resistant, shock-resistant and flexural-resistant cable sheath materials prepared in Examples 4-6 and Comparative Examples 1-3 was tested in accordance with ISO178 standard "Determination of Flexural Properties of Plastics".

[0073] 5. The flexural resistance of the heat-resistant and impact-resistant flexural cable sheath materials prepared in Examples 4-6 and Comparative Examples 1-3 was tested using a flexural testing machine. The specific test results are shown in Table 1:

[0074] Table 1- Sample performance test data table

[0075]

[0076] Data Analysis:

[0077] Comparative analysis of the data in Table 1 shows that the heat-resistant, impact-resistant and flexural-resistant cable sheath materials prepared in Examples 4-6 have excellent heat resistance, mechanical properties, impact resistance and flexural resistance.

[0078] In Comparative Example 1, butadiene epoxy resin is used to replace olefin copolymer, and methacrylate with flexibility is lacking, so that the impact toughness and flexural resistance of the prepared cable sheath material are significantly reduced.

[0079] In Comparative Example 2, polyethylene was used to replace silane cross-linked polyethylene, and polysilicon chlorine organic bodies containing polybenzene and polysilicon elements were lacking, and the mechanical properties of the cable sheath material were significantly reduced, which was manifested in the reduction of tensile strength and elongation at break. In Comparative Example 3, no mixed inorganic filler was added to the prepared cable sheath material, which reduced the mechanical strength and heat resistance of the prepared cable sheath material, which was manifested in the increase of the thermal aging mass loss rate and the decrease of tensile strength, elongation at break and impact toughness.

[0080] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0081] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0082] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A heat-resistant, impact-resistant, flex-resistant cable sheath material, characterized in that: The invention comprises, by weight, 50-60 parts of silane cross-linked polyethylene, 20-30 parts of olefin copolymer, 5-10 parts of mixed inorganic filler, 1-2 parts of alkali-free glass fiber, 1-2 parts of heat stabilizer, 1-2 parts of plasticizer, 1-2 parts of antioxidant and 1-2 parts of light stabilizer; The preparation method of the silane cross-linked polyethylene comprises the following steps: A1. 4-tert-butylcatechol and carbon tetrachloride are mixed and dissolved to obtain a 4-tert-butylcatechol solution; a packing column is connected to one side of a three-necked round-bottom flask, the upper end of the packing column is connected to a condenser, and the lower end is connected to a reflux bottle; cooling medium water is introduced into the condenser, and 1 / 3 volume of petroleum ether is filled in the reflux bottle; the reflux bottle is heated to 30-40°C; A2, two ports of the three-necked round-bottom flask are connected to a dropping metering bottle, and the dropping metering bottle is respectively filled with p-tert-butylcatechol solution and trichlorosilane, both of which are added dropwise to the three-necked round-bottom flask at 1 mL / min; then reflux reaction is carried out at 25-30° C. for 4-6 hours, and the byproduct hydrogen chloride gas is discharged through the condenser of the packed column, and after post-process treatment, a polysilicon chlorine organic body is obtained; A3, polysilicon chlorine organic body, initiator, polyethylene and water are mixed, polycondensed and cross-linked at 70-80°C for 24 hours, and then filtered to obtain silane cross-linked polyethylene; The preparation method of the olefin copolymer comprises the following steps: The epoxidized polybutadiene resin, methacrylic acid and a catalyst are mixed and reacted at 30-40° C. for 3-5 hours to obtain a product; the product is filtered using a filter cloth to remove the catalyst solids to obtain an olefin copolymer; The mixed inorganic filler is prepared by the following steps: Diatomaceous earth, fly ash floating beads, 0.2-1 mm alumina hollow microspheres, and 0.5-1 mm magnesium oxide hollow microspheres are uniformly mixed to obtain a mixture; the mixture is ground to 100-200 nm to obtain a mixed inorganic filler.

2. The heat-resistant, impact-resistant, flex-resistant cable sheath material according to claim 1, characterized in that: In step A1, the dosage ratio of p-tert-butylcatechol and carbon tetrachloride is 20-30 g:50 mL; in step A2, the dosage of p-tert-butylcatechol solution is 70-80 mL, and the dosage of trichlorosilane is 5-10 g; The post-process treatment includes: heating a three-necked round-bottom flask to 80-85° C. until all organic liquids are evaporated, and collecting solid products; washing the solid products with deionized water, and vacuum drying at 70-80° C. to constant weight to obtain polysilicon chlorine organic bodies.

3. The heat-resistant, impact-resistant, flex-resistant cable sheath material according to claim 2, characterized in that: In step A3, the initiator is dibutyltin dilaurate; the dosage ratio of polysilicon chloride organic body, initiator, polyethylene and water is 50-60g:1-3g:300g:500mL.

4. The heat-resistant, impact-resistant, flex-resistant cable sheath material according to claim 1, characterized in that: The usage ratio of epoxidized polybutadiene resin, methacrylic acid and catalyst is 50-100g:10-20g:1-3g.

5. The heat-resistant, impact-resistant, flex-resistant cable sheath material according to claim 1, characterized in that: The diameter of the alkali-free glass fiber is 10-20 μm; the heat stabilizer is obtained by mixing dibutyltin maleate and phosphite in a mass ratio of 2-3:1; the plasticizer is any one of methyl phthalate, ethyl phthalate or butyl phthaloyl glycolate; the antioxidant is obtained by mixing antioxidant 1010 and antioxidant DSTP in a mass ratio of 2-3:1; the light stabilizer is obtained by mixing UV-9 and UV-531 in a mass ratio of 1:

1.

6. A method for preparing a heat-resistant, impact-resistant, flex-resistant cable sheath material according to any one of claims 1 to 5, characterized in that: The following steps are involved: B1, uniformly mixing silane cross-linked polyethylene, olefin copolymer, mixed inorganic filler, alkali-free glass fiber, heat stabilizer, plasticizer, antioxidant and light stabilizer to obtain a mixture; B2. The mixed materials are melt-blended on a double-roll mill to obtain a sample; the sample is placed on a flat vulcanizer for hot pressing and cold pressing in sequence, and then naturally cooled to room temperature to obtain a heat-resistant, impact-resistant, and flex-resistant cable sheath material.

7. The method for preparing a heat-resistant, impact-resistant and flex-resistant cable sheath material according to claim 6, characterized in that: In step B2, the temperature of melt blending is 100-110°C, and the time of melt blending is 10 min; the temperature of hot pressing is 110-120°C, the pressure of hot pressing is 10-20 MPa, and the time of hot pressing is 3-5 min; the temperature of cold pressing is 25°C, the pressure of cold pressing is 10 MPa, and the time of cold pressing is 3-5 min.

Citation Information

Patent Citations

  • Silane crosslinked semiconductive shielding material and preparation method thereof, and application of silane crosslinked semiconductive shielding material

    CN110938274A